Common Hair Problems and their Homoeopathic Management (Homoeopathy for All, 2021)
Hair loss from the hairy areas of the body is medically termed as Alopecia. Hair plays an important role in the person’s presentation and appearance. Lack of hair density or patchy hair is a disease and may affect the self-esteem, personality and relationship.Between both genders, hair loss or alopecia is one of the most common problems as they age. For many people, it starts to begin around the age of 30 in 25% of men and about 70% hair are lost by age of 60 years.1About 80% of men show signs of male pattern baldness by age 70 years.2 In most cases, it develops gradually. As per reports, the average scalp contains about 100,000 hairs and usually 100 hairs may fall out daily. Almost entire human body is covered by hair of varying thickness and colour except lips, palms and soles.The common cause of hair loss are nutritional deficiencies, hormonal imbalance, thyroid issues, polycystic ovary syndrome (pcos), birth control pills/ medication, stress, and hairstyling products. Environment, lifestyle and food habits also play a vital role. Excessive loss of hair seeking medical intervention. All hair loss problems are not curable some are only controllable. Conventional treatment does not have any effective treatment. However, medicines like finasteride and minoxidil used by conventional treatment have many side effects.Homoeopathy works on the root cause and helps in the treatment of hair loss. In this article, we will discuss about home management of different types of hair loss, home care of hair loss and homoeopathic therapeutics with its indication.
Keywords: self-esteem; Diet; Stress